Mild hypoxia-induced structural and functional changes of the hippocampal network - Hencz, Alexandra; Magony, Andor; Thomas, Chloe; Kovacs, Krisztina; Szilagyi, Gabor; Pal, Jozsef; Sik, Attila (Frontiers in Cellular Neuroscience, 2023)
Hypoxia causes structural and functional changes in several brain regions, including the oxygen-concentration-sensitive hippocampus. We investigated the consequences of mild short-term hypoxia on rat hippocampus in vivo. The hypoxic group was treated with 16% O2 for 1 hour, and the control group with 21% O2. Using a combination of Gallyas silver impregnation histochemistry revealing damaged neurons and interneuron-specific immunohistochemistry, we found that somatostatin-expressing inhibitory neurons in the hilus were injured. We used 32-channel silicon probe arrays to record network oscillations and unit activity from the hippocampal layers under anaesthesia. There were no changes in the frequency power of slow, theta, beta, or gamma bands, but we found a significant increase in the frequency of slow oscillation (2.1-2.2 Hz) at 16% O2 compared to 21% O2. In the hilus region, the firing frequency of unidentified interneurons decreased. In the CA3 region, the firing frequency of some unidentified interneurons decreased while the activity of other interneurons increased. The activity of pyramidal cells increased both in the CA1 and CA3 regions. In addition, the regularity of CA1, CA3 pyramidal cells’ and CA3 type II and hilar interneuron activity has significantly changed in hypoxic conditions. In summary, a low O2 environment caused profound changes in the state of hippocampal excitatory and inhibitory neurons and network activity, indicating potential changes in information processing caused by mild short-term hypoxia.